Beginning Java 8 APIs, extensions and libraries Swing, JavaFX, JavaScript, JDBC and network programming APIs - Sharan, Kishori; Friesen, Jeff (New York friends of ED/Apress, 2014)
This book is a comprehensive approach to learning the Java programming language extensions and available APIs and libraries. Coverage includes: applying Java Swing for building Java front ends or user interfaces (UIs); building small Java applications (applets); Java network programming; connecting with databases using JDBC APIs; working with JavaFX, RMI (Remote Method Invocation), and JNI (Java Native Interface); and using scripting in Java, including coverage of the Nashorn engine. Each topic includes a discussion of the topic's background; a step-by-step process, with small snippets of Java code; and a complete and ready-to-run Java program. Over 130 images and diagrams help visualize and better understand the topics. More than 130 complete programs allow the reader to practice and quickly learn the topics. This resource is for Java programmers who are familiar with the fundamentals of the Java language and Java programming. - -
Includes index
2
NEW
Keywords: Application program interfaces (Computer software); Java (Computer program language); Libraries (Computer program subroutines); Object-oriented programming (Computer science)